Investigasi Kasus Kejadian Luar Biasa Leptospirosis Di Probolinggo Tahun 2022 - Wulandari, Heni Surya; Hendrati, Lucia Yovita (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
Leptospirosis is a zoonotic disease transmitted by the bacteria Leptospira sp. Several areas in Indonesia have become endemic, one of which is in Probolinggo. In addition, this location is a flood-prone area and place for rat sentinel surveillance in the East Java region. The purpose of this study was to describe the results of the investigation of the Leptospirosis outbreak in Probolinggo. The study used a descriptive with a case report design on Leptospirosis cases between January to February 2022. The case was derived from the results of Leptospirosis surveillance confirmation data. Based on the findings in January, a high incidence of Leptospirosis was reported and continues to be reported as W1 to the Health Office. Results showed from the investigation of the outbreak there were three cases, male patients, with jobs as traders, retirees, and farmers. The first case resides in Maron District, the second case in Kanigaran District, and the third case in Mayangan District. Most cases were diagnosed as probable (67%) and others as suspect (33%). The three cases had almost the same symptoms such as dizziness, fever, yellow eyes, and muscle aches throughout the body. Two of the three cases were declared dead. It can be concluded that Probolinggo designated as an outbreak of Leptospirosis in 2022. The leptospirosis sentinel surveillance activities carried out were able to detect outbreaks.